Pengembangan bahan ajar matematika berbasis discovery learning pada materi perbandingan SMP - Izza Rahmawati; Alzaber Alzaber; Sari Herlina; Lilis Marina Angraini (Journal of Didactic Mathematics, 2022)
The purpose of this research is to produce mathematics teaching materials in the form of Discovery Learning-based modules on comparative materials for SMP class VII that have been tested for validity. This research uses the development method with the ADDIE development model, which includes; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. However, due to the COVID-19 pandemic situation, the ADDIE development model was carried out in only three stages, namely; 1) Analysis, 2) Design, 3) Development. This study uses an instrument in the form of a LKPD validation sheet. While the data collection technique used is validation data from 2 Mathematics Education lecturers and 1 mathematics teacher at SMPN 4 DUMAI. The data analysis technique used is descriptive qualitative analysis. The results showed that the module developed by both material and media experts was Very valid and valid with a value of 88.08% and 84.88%, respectively. Based on the results obtained, it can be concluded that the module based on Discovery Learning on comparative material in class VII has been tested for validity.